How to Be Freed from a Leadership Curse? A Political ‘Code of Conduct’ by the Nandi Council of Elders during the 2013 Elections in Kenya - (:unkn) unknown (My University, 2020)
In April 2012, more than a year before Kenya’s 2013 elections, the Nandi Kaburwo Council of Elders in Nandi Hills undertook the original task of writing the Nandi County Political Code of Conduct (NCPCC). Throughout Kenya, the pre-election period was characterized by a significant involvement of councils of elders in spreading messages of peace and promoting “good leadership,” unlike 2007 when these councils played an active role in mobilizing Kenyans to take part in the post-electoral violence. Printed as an 8-page booklet, the NCPCC was targeting local candidates, their supporters and political parties. It displayed regulations aimed to contribute to the “transformation of Nandi County” into a prosperous place, an “island of new politics, free of political madness.” Inspired from the role models of the Kenyan “Goodwill Ambassadors” for peace put in place in 2012, and based on oral narratives about iconic pre-colonial Nandi leaders—such as Kimnyolei and Koitalel Samoei—, this code of conduct brings to light cultural, social, economic and political dynamics mobilized by a wide range of actors (NGO, elders, candidates, entrepreneurs) during electoral times. Therefore, I believe it is crucial for the researcher to present and analyze it as a primary source that illustrates the aspirations and strategies of a local elite with their own conception of leadership. More broadly, through this original document, one can question the role played by councils of elders in Kenyan politics from a grassroots perspective, as well as the role they play in “re-inventing” their political history under the guise of preserving traditions.
Keywords: African Research